KAJIAN PENERAPAN KONSEP PASSIVE COOLING PADA BANGUNAN HOTEL ARJUNA BATU - Gabriel Steven; Afif Fajar Zakariya (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2024)
Abstract: The tourism sector plays a vital role in regional economic growth, with accommodation, particularly hotels, acting as a key element in attracting and accommodating visitors. In popular destinations like Kota Batu, East Java, high demand for hotel rooms often leads to limited availability. This emphasizes the need for hotel development to prioritize sustainability, including energy efficiency, to mitigate the impact of global warming. This research focuses on the importance of implementing passive cooling in hotel design as a key strategy for achieving this goal. Kota Batu, with its generally cool temperatures, presents an ideal opportunity to utilize natural resources effectively and minimize reliance on excessive energy consumption. This study employs qualitative research methods, drawing insights from relevant journals to gain a comprehensive understanding of the area and the specific hotel buildings being analyzed. The aim is to provide recommendations for the most suitable design types for implementing passive cooling in Kota Batu's hotels. This would not only ensure the comfort and satisfaction of tourists but also contribute to environmental sustainability and support long-term economic growth in the region.Keyword: Batu, Hotel, Passive Cooling Abstrak: Sektor pariwisata memegang peran penting dalam pertumbuhan ekonomi suatu daerah, dengan penginapan, khususnya hotel, menjadi elemen kunci dalam menarik wisatawan. Tingginya permintaan kamar hotel, terutama di destinasi populer seperti Kota Batu, Jawa Timur, seringkali mengakibatkan ketersediaan kamar yang terbatas. Oleh karena itu, pembangunan hotel harus memperhatikan keberlanjutan, termasuk efisiensi energi untuk mengurangi dampak pemanasan global. Pentingnya penerapan pendinginan pasif dalam desain hotel menjadi fokus penelitian. Kota Batu, dengan suhu yang cenderung sejuk, memiliki potensi untuk memanfaatkan sumber daya alam secara optimal tanpa bergantung pada energi berlebih. Melalui metode penelitian kualitatif, penelitian ini mengacu pada jurnal-jurnal terkait untuk mendapatkan pemahaman mendalam tentang daerah dan objek penelitian. Diharapkan hasil penelitian ini dapat memberikan panduan mengenai jenis desain yang paling sesuai untuk menerapkan pendinginan pasif dalam bangunan hotel di Kota Batu, sehingga tidak hanya memenuhi kebutuhan wisatawan, tetapi juga mendukung keberlanjutan lingkungan dan pertumbuhan ekonomi yang berkelanjutan.Kata Kunci: Batu, Hotel, Pendinginan Pasif